Socialization of the Drug Awareness Family Movement: DAGUSIBU to PKK Members in Pandeyan Village, Boyolali Regency, Central Java - Olivia Murlitta (Universitas Sahid Surakarta, 2024)
Abstract : DAGUSIBU is an abbreviation of DA (get medicine correctly), GU (Use medicine correctly), SI (Store Medicine correctly) and BU (Dispose of medicine correctly). The level of knowledge of the Pandeyan Village community regarding how to use and store medicine is still relatively low. It is hoped that DAGUSIBU's socialization activities will make people care and realize the importance of health through good and correct medication management procedures. The method in this activity is carried out through socialization with presentations and questions and answers related to drug management material. The socialization went smoothly and the participants looked enthusiastic in how they received the message and asked questions about the method getting, how to use medicines, checking expiration dates and how to properly dispose of expired medicines. From this activity, it is hoped that participants will be able to apply DAGUSIBU to their families and environment. Keywords: Dagusibu, Socialization, Medicine